Security framework for dynamic service-oriented IT systems. Issue 4 (2nd October 2018) - Kołaczek, Grzegorz; Mizera-Pietraszko, Jolanta
ABSTRACT: The paper proposes a framework for dynamic service-oriented IT systems security. We review the context of service-oriented architecture (SOA), which constitutes a paradigm of dynamic system configuration including security constraints at the system module development stage, supporting with the domain-driven resources, carrying out routine SOA maintenance and implementing XML-compatible parsing technologies in order to improve the system performance. Likewise, we discuss the fundamental differences between security management systems with traditional centralized and monolithic architecture and service-oriented IT systems from the perspective of security-related issues. Web services security becomes fairly crucial, in particular, when it relates to distributed system environments. Our multi-layered reference framework for service-oriented systems is aimed at principal objectives predominantly related to IT systems security working in dynamic environments. Furthermore, we carry out an in-depth security analysis of a multi-agent system design dedicated to work in the service-oriented environments. Finally, we conclude briefly with the findings of our study on IT security requirements and performance on the comparison basis of correlation between the observations at the low and at high layers of our reference security model. The paper is an extended version of INISTA 2017 paper [Kołaczek, G., & Mizera-Pietraszko, J. (2017) and presents more detailed related works overview, explanation of the subjective logic application in the process of security level evaluation and extensive discussion of the obtained results and their role in SOA security level modelling.